An LC–MS-based metabolomic approach provides insights into the metabolite profiles of Ginkgo biloba L. at different developmental stages and in various organs. (September 2022) - Guo, Jing; Wu, Yaqiong; Jiang, Mingjun; Wu, Changfeng; Wang, Guibin
Graphical abstract: Highlights: Comprehensive metabolites profiles in the ginkgo leaves and seeds were identified. The development stages had greater impact on the metabolites pathways and profiles. 653 flavonoid metabolites were identified and some new components were reported. Albanin G and neolinderatin had most significant difference among the leaf samples. 8 most significant differential flavonoid metabolites were detected in SE vs JE. Abstract: Ginkgo ( Ginkgo biloba L.) is a tree valued for the high medicinal and nutritional value of its leaves and seeds. However, the metabolite profiles of ginkgo leaves and seeds and their changes during development have not been comprehensively analyzed, which hinders improvements in the utilization of ginkgo. A comprehensive and systematic untargeted LC–MS metabolomics analysis of the metabolites in ginkgo leaves (male and female) and seeds at two developmental stages identified 8146 known metabolites, which mainly included lipids and lipid-like molecules, phenylpropanoids and polyketides, organoheterocyclic compounds, organic acids and derivatives, organic oxygen compounds, and benzenoids. Some of the identified metabolites have known healthcare and food value, and some of the others are newly discovered metabolites with potential for new drug development. The small number of differential Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways between leaves of male and female gingko trees indicated that the developmental stage affected the metabolic pathways more significantly than sex. Among the flavonoid constituents of ginkgo, 653 flavonoid metabolites were identified, and these included some new flavonoid components, which confirmed that the developmental stage is a critical factor in secondary metabolite variations. This study illuminated the metabolites and medicinal and edible values of ginkgo leaves and seeds at different developmental stages and thus supports further effective utilization of ginkgo leaves and seeds.